The Role of Customer Experience, Ease of Use, and Customer Trust in Forming Repurchase Intention in Access by KAI Application Users - Sulasih, Ragil; Ekowati, Titin; Wijayanti, Wijayanti (ProBisnis : Jurnal Manajemen, 2025)
The continuous advancement of technology has triggered the emergence of more e-commerce platforms, which significantly affect the way people transact online. The increasingly tight competition in the transportation services business, so companies continue to strive to provide improved services to upgrade applications to build repurchase intention in consumers through customer experience, ease of use, and customer trust. This phenomenon is very important to be considered by PT KAI as one of the transportation service providers in Indonesia. This study aims to test the effect of customer experience, ease of use and customer trust on repurchase intention. This quantitative study uses a survey design to collect data. The population in the study all users of the Access by KAI application. The sample taken in this study amounted to 150 respondents who were determined using the purposive sampling technique. Data collection was carried out using a questionnaire measured with a likert scale that was answered completely, according to the criteria and had met the validity and realibility requirements. Data analysis was carried out using multiple linear regression analysis. The result of study show that customer experience, ease of use, and customer trust have a positive and significant effect in partially.